Analisis Himbauan MUI (Boikot Produk Pro-Israel) Terhadap Perilaku Konsumsi - Silvia, Khofifah Junisa; Mu’awwanah, Uliyatul (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This research study the impact of boycott pro-Israel products on consumption behavior at Dailie Mart, a shopping center in Puger District, Jember Regency. This study uses a quantitative method with an associative approach, measuring the relationship between the variables of boycott pro-Israel products (free variables) and consumption behavior (bound variables). The data was accumulated into 97 respondents through a questionnaire distributed by Dailie Mart consumers. The results of a simple linear regression analysis stated that there was a positive and significant impact between the boycott of pro-Israel products on consumption behavior. The higher the boycott rate, the greater the change in people's consumption behavior. A beta value of 0.819 indicates a strong influence. The study also found that 67% of changes in Consumption Behavior can be explained by the Product Boycott variable. This research highlights the importance of ongoing education to consumers about products affiliated with Israel and the importance of boycotts based on Islamic economic values. Retailers like Dailie Mart are expected to provide clear information about local alternative products that are halal and are not affiliated with Israel.